NOTES ON THE BIOLOGY OF CERTAIN SNAIL-KILLING FLIES (SCIOMYZIDAE) - LV.Knutson; ER.Shahgudian; GH.Sahba (Tehran University of Medical Sciences, 1973)
The paper contains the first report on the biology of snail-killing flies (sciomyzidae) in Khuzestan. It is based on field and laboratory studies conducted during November 1971 and April 1973, as well as field observations in May 1972, at the Dezful Medical Research Station. Additional biological information obtained during studies is given for Pherbellia fuscipes (Macaquart), P.grisescens (Meigen), Coremacera amoena (Loew), Knutsonia turkestanica (Hendel), Sepedon sphegea (Fabricius), S.s spinipes (Scopoli) and Colobaea iranica Knutson, together with their habitat distribution.